Effects of Chronic Tinnitus on Metabolic and Structural Changes in Subjects With Mild Cognitive Impairment - Lee, Sang-Yeon; Kim, Heejung; Lee, Jun Young; Kim, Ju Hye; Lee, Dong Young; Mook-Jung, Inhee; Kim, Young Ho; Kim, Yu Kyeong (Frontiers in Aging Neuroscience, 2020)
Tinnitus is a conscious auditory perception in the absence of an external stimulus. Despite previous reports of a recognized association between tinnitus and cognitive deficits, the effects of tinnitus on functional and structural brain changes associated with cognitive deficits remain unknown. We aimed to investigate the changes in glucose metabolism and gray matter (GM) volume in subjects diagnosed with mild cognitive impairment (MCI) depending on tinnitus. Twenty-three subjects were subclassified into MCI with the chronic tinnitus (MCI_T) and MCI without tinnitus (MCI_NT) groups. Encouraged by the identification of neural substrates associated with tinnitus and cognitive deficits, we correlated the extent of tinnitus severity with the changes in glucose metabolism and GM volume and conducted a glucose metabolic connectivity study. Compared to the MCI_NT group, the MCI_T group showed significantly lower metabolism in the right superior temporal pole and left fusiform gyrus. Additionally, the GM volume in the right insula was markedly lower in the MCI_T group compared to the MCI_NT group. Moreover, correlation analyses in metabolism or GM volumes revealed specific brain regions associated with the cognitive decline with increasing tinnitus severity. Metabolic connectivity analysis revealed that MCI_NT had markedly strengthened intra-hemispheric connectivity in the frontal, parietal, and occipital regions than did MCI_T. Furthermore, MCI_NT showed a strong negative association between the parietal and temporal and parietal and limbic regions, but the association was not observed in MCI_T. These findings indicate that tinnitus may cause metabolic and structural changes in the brain and alters complex inter- or intra-hemispheric networks in MCI. Considering the impact of MCI on accelerating dementia, these results provide a valuable basis on which yet-to-be-identified neurodegenerative markers of tinnitus can be refined.